Tamsulosin And Corticosteroid In The Medical Expulsive Therapy For Distal Ureteral Stones: A Prospective Comparative Study - KC, Hari Bahadur; Sharma, Suman (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Medical Expulsive Therapy (MET) has become an established treatment option for small ureteral stones. While alpha blockers are commonly used agents, the addition of anti-inflammatory medications such as corticosteroids seems to increase efficacy. This study aims to know the efficacy of the addition of a corticosteroid prednisolone, to tamsulosin in the medical management of symptomatic distal ureteral calculi. Methods: In this prospective study, patients with symptomatic distal ureteral stones of size 5 to 10mm were randomly assigned to two groups: group A received tamsulosin 0.4 mg and group B received tamsulosin 0.4 mg plus prednisolone 30 mg for 2 weeks. The number of colicky pain episodes, stone expulsion rate, time to stone expulsion, analgesic use, and side effects of drugs were noted in both groups. Statistical analysis was carried out using Student’s t-test and chi-square test. Results: Total of 120 patients (59 in group A and 61 in group B) were enrolled in the study and their average age was 32.13±10.5 years and male: female ratio was 1.55:1. There was a significantly higher rate of stone expulsion in tamsulosin plus prednisolone group than in tamsulosin alone group (82.0% vs. 64.4%, p=0.03). The demographic profiles, baseline investigations, stone size, pain score, analgesic used, and occurrence of side effects were comparable between the two groups. Conclusions: The combination of tamsulosin with prednisolone has significantly higher stone expulsion rate than tamsulosin as a medical expulsive therapy. Hence, this combination seems to be effective and safe for the treatment of distal ureteral stones.